Editorial Introduction to Pedagogy & (Im)Possibilities across Education Research - J. Spencer Clark (Pedagogy & (Im)Possibilities across Education Research, 2017)
The editorial board is excited to publish our first issue of Pedagogy & (Im)Possibilities across Education Research. We have spent nearly a year conceptualizing, shaping, and producing the journal and this first issue. We hope you find it engaging and thought provoking. We, therefore, formally welcome submissions to the journal and look forward to facilitating the advancement of research in education.
Keywords: Education; Pedagogy; Education Research